1992
DOI: 10.2172/6575260
|View full text |Cite
|
Sign up to set email alerts
|

Status report on the geology of the Oak Ridge Reservation

Abstract: Simplified tectonic map of the southern Appalachians showing the location of the Oak Ridge Reservation .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 49 publications
1
48
0
Order By: Relevance
“…Saprolite is a material formed by extensive in situ weathering of an existing parent rock, which still retains geologic features from the parent rock (Bates and Jackson, 1987). In addition to bedrock features, such as sedimentary layering and tectonic fractures, saprolite often contains soil features such as high matrix porosity, translocated or illuvial clays, neoformed clay minerals, Fe/Mn oxides, and marks of bioturbation (Dreier et al, 1987;Hatcher et al, 1992;Buol, 1994;Graham et al, 1994;Stolt and Baker, 1994;Richter and Markewitz, 1995;Driese et al, 2001). Some authors maintain that a material must weather isovolumetrically (i.e., with little or no volume change) before it should be referred to as saprolite (Gardner, 1980(Gardner, , 1992(Gardner, , 2000Velbel, 1990).…”
Section: Introduction and Review Of Previous Sedimentary Rock Saprolimentioning
confidence: 99%
See 1 more Smart Citation
“…Saprolite is a material formed by extensive in situ weathering of an existing parent rock, which still retains geologic features from the parent rock (Bates and Jackson, 1987). In addition to bedrock features, such as sedimentary layering and tectonic fractures, saprolite often contains soil features such as high matrix porosity, translocated or illuvial clays, neoformed clay minerals, Fe/Mn oxides, and marks of bioturbation (Dreier et al, 1987;Hatcher et al, 1992;Buol, 1994;Graham et al, 1994;Stolt and Baker, 1994;Richter and Markewitz, 1995;Driese et al, 2001). Some authors maintain that a material must weather isovolumetrically (i.e., with little or no volume change) before it should be referred to as saprolite (Gardner, 1980(Gardner, , 1992(Gardner, , 2000Velbel, 1990).…”
Section: Introduction and Review Of Previous Sedimentary Rock Saprolimentioning
confidence: 99%
“…Most of the studies were carried out at four research sites (Melton Branch, Waste Area Grouping 5, Burial Ground 4, and West Bear Creek Valley) situated in weathered materials derived from calcite-rich shale or siltstone bedrock of the middle to upper Cambrian age Conasauga Group (Hatcher et al, 1992). Most of the studies were funded by the Department of Energy (DOE) and were related to efforts to clean up or control migration of hazardous and radioactive wastes from shallow waste burial pits located in these materials.…”
Section: Introduction and Review Of Previous Sedimentary Rock Saprolimentioning
confidence: 99%
“…6, reflecting the higher velocity of unweathered limestone compared with that of shale. Figure 6 suggests, however, that a few parts of the Nolichucky, where the dark blue patches appear, exhibit velocities similar to that of the Maynardville-perhaps these represent the carbonate subunits within the Nolichucky (Hatcher et al 1992).…”
Section: Imaging the Maynardville/nolichucky Contactmentioning
confidence: 97%
“…A detailed map of the study area is shown in Fig. 2 (Hatcher et al 1992). These rocks, which strike between N47°E and N67°E, have an average dip of 43°to the southeast Hatcher et al 1992).…”
Section: Geological and Hydrogeological Settingmentioning
confidence: 99%
See 1 more Smart Citation